Early Childhood Science Development Through Experiments on Mixing Colors with Water Media at Al Irsyad Banyuwangi Kindergarten Age Group 5-6 Years - Fidya Salim Bakrisuk; Ruqoyyah Fitri (SEA-CECCEP, 2024)
Early childhood is crucial for fostering curiosity and interest in science. This research aims to examine the development of early childhood science through experiments mixing colors with water as a medium at the Al Irsyad Banyuwangi Kindergarten in the 5–6-year age group. This research uses a qualitative method with a case study approach. Data collection was carried out through observation, interviews, and documentation. Data analysis was carried out using qualitative descriptive analysis techniques. The research results show that the experiment of mixing colors with water as a medium is effective in developing early childhood science, including aspects of knowledge, scientific processes, and scientific attitudes. In the knowledge aspect, children can recognize primary, secondary, and tertiary colors well. In the scientific process aspect, they are skilled in carrying out observations, experiments, and communication. In the scientific attitude aspect, children show increased curiosity, creativity and critical thinking. An interesting finding is the child's ability to discover new colors from primary colors and apply them in everyday life, such as when painting and drawing. This shows that this experiment can foster creativity and problem solving in children. In conclusion, the experiment of mixing colors with water as a medium is an appropriate strategy for developing science in early childhood, especially in the aspects of knowledge, scientific processes and scientific attitudes.